Upscaled Synthesis of n‐ and p‐Type Thermoelectric Skutterudite Single Legs by Gas Atomization and Current‐Assisted Sintering. Issue 17 (23rd April 2018) - Stiewe, Christian; Sottong, Reinhard; de Boor, Johannes; Müller, Eckhard
Abstract : CoSb3 ‐based Skutterudites are among the best materials for thermoelectric generator (TEG) applications in the intermediate temperature range up to 500 °C. Synthesis of these materials is usually performed on a laboratory scale in materials research. In order to be suitable for an industrial low cost production of TEG technologies capable of delivering large amounts of thermoelectric (TE) materials are needed. A process mastering this challenge is gas atomization, which has been adapted to the requirements of TE materials, in particular CoSb3 ‐based Skutterudites .It is found that despite rapid solidification taking place in the atomization process the produced powder material contains only traces of the target Skutterudite phase. Microstructure investigation shows a very fine dispersion on the micrometer scale of CoSb, CoSb2, and Sb phases in the atomized particles, making diffusion paths for the formation of the Skutterudite phase short. This allows the use of short‐term heat treatment to achieve almost single phase material of high functional homogeneity. Different thermal post‐treatments are evaluated leading to a content of >98% of the Skutterudite phase in large ingots. Doping and filling by varying the starting composition is applied to tune the materials to n‐ and p‐type conduction, respectively, and led to an increase of their thermoelectric figure of merit ZT up to values of 0.9 and 0.72 for n‐ and p‐type material, respectively. Abstract : Gas atomization can be used in combination with current‐assisted hot pressing to produce p‐ and n‐type Skutterudite single legs in large quantities in comparably short time. The results on ZT shown in the present work are measured on still not optimized materials and prove the possibility of Skutterudites fabrication by gas atomization with moderate ZT values.